Resistance of Advanced Soybean Lines to Pod Borrer (Etiella zinckenella) - Heru Kuswantoro; Marida S. Y. I. Bayu; Yuliantoro Baliadi; Wedanimbi Tengkano (Biosaintifika: Journal of Biology & Biology Education, 2017)
The increasing and stabilizing of soybean product in Indonesia face many limitations. One of the limiting factors is pod borrer (Etiella zinckenella Treitschke) infestation that is able to cause yield loss up to 80%. Objective of the research was to find out some advanced soybean lines that resistant to pod borrer. Design was randomized complete block with three replications. Soybean lines were grown gradualy to ensure the simultanously flowering. The plants were caged at 35 days after planting (DAT) and infested with the imago of E. zinckenella at 56 DAT. Results showed that different soybean lines affected imago population, eggs population, larvae population, infected pods and infected seeds. Some genotypes were consistantly resistant to E. zinckenella. The resistance of those genotypes were non preference resistance based on eggs population, larvae population, infected pod and infected seeds. This study discovered nine soybean lines that is resistant to E. zinckenella, so that it can be beneficial for improving soybean resistance to this pest through releasing as a new resistant pod borer variety after tested further in potential yield and genetic x environment interaction trials. In addition, there were three varieties and two germplasm accessions that can be used as gene sources for improving the resistance of the varieties. The three varieties are able to be cultivated directly in field to decrease the E. zinckenella occurrence.